The Influence of Transformational Leadership and Organizational Citizenship Behavior on Employee Performance with Work Passion as Moderation - Ndruru, Hermawan Susanto; Abadi, Ferryal (Yayasan Sinergi Kawula Muda, 2024)
The creative industry has emerged as a rapidly growing sector in the global economy, with the challenge of maintaining employee performance being a primary concern. This study investigates the impact of Transformational Leadership and Organizational Citizenship Behavior (OCB) on Employee Performance, with Work Passion as a moderating factor. Data were collected from 220 employees in the creative divisions of television media companies in Jakarta, chosen through purposive sampling, and analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that Transformational Leadership significantly enhances OCB, positively affecting Employee Performance. Work Passion, a crucial element in this study, strengthens the impact of OCB on Employee Performance, indicating its crucial role in fostering innovation, quality, and dedication in the creative industry. These findings suggest that industry practitioners should focus on psychological factors like Work Passion to maximise the benefits of transformational leadership and OCB in improving employee performance. The implications highlight the need for leaders to communicate a clear vision and foster an environment where work passion can thrive, ultimately leading to superior performance outcomes.